The overparenting solution : raising resourceful children to meet today's challenges - Glass, George S.; Tabatsky, David (Rowman & Littlefield, 2021)
"When parents intervene inappropriately and/or excessively, their children may grow up and behave badly, plagued by anxiety, narcissism and feelings of entitlement as they struggle to cope with everyday life. The Overparenting Solution offers alternatives for parents to check their ambitions at the door and do what's best for their kids"--